2017
DOI: 10.1002/ps.4481
|View full text |Cite
|
Sign up to set email alerts
|

Dibenzo-α-pyrones: a new class of larvicidal metabolites againstAedes aegyptifrom the endophytic fungusHyalodendriellasp. Ponipodef12

Abstract: Our study revealed dibenzo-α-pyrones to be a new class of larvicidal metabolites against A. aegypti. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…The lowest MIC observed from A. pullulans was 0.17 mg/mL. Hyalodendriella sp., has been reported to contain bioactive properties that inhibit bacterial growth [28,43] and fungal growth [44]. This validates the results we obtained in this study, that fungal endophytes from plants have the potential to inhibit microorganisms other than bacteria, such as fungi.…”
Section: Discussionsupporting
confidence: 91%
“…The lowest MIC observed from A. pullulans was 0.17 mg/mL. Hyalodendriella sp., has been reported to contain bioactive properties that inhibit bacterial growth [28,43] and fungal growth [44]. This validates the results we obtained in this study, that fungal endophytes from plants have the potential to inhibit microorganisms other than bacteria, such as fungi.…”
Section: Discussionsupporting
confidence: 91%
“…Ponipodef 12 associated with the healthy stems of the “Neva” hybrid of Populus deltoides Marsh × P. nigra L. were collected from Longhua in Hebei Province of China. Compound 83 displayed antifungal effects against the spore germination of M. oryzae with potent inhibition with the IC 50 value of 11.6 µg/mL, which was comparable with the positive control, carbendazim (IC 50 6.9 µg/mL) [ 50 ]. Previously, it found that rhizopycnin D ( 84 ), palmariol B ( 85 ), TMC-264 ( 86 ), penicilliumolide B ( 87 ), and alternariol 9-methyl ether ( 88 ) exhibits antifungal activity against the spore germination of M. oryzae [ 51 , 52 ].…”
Section: Medicinal Plantsmentioning
confidence: 99%
“…was an interesting producer of larvicidal metabolites. Previously, dibenzo-α-pyrones were identified from this fungus as potent inhibitors of A. aegypti larvae [10]. In the current study, a new structural type of larvicidal metabolites was identified from the same species.…”
Section: Larvicidal Activitiesmentioning
confidence: 68%
“…Ponipodef12 was isolated as an endophytic fungus from the hybrid poplar of Populus deltoides × P. nigra [9]. This endophytic fungus was known to produce benzo-α-pyrones, dibenzo-α-pyrones [10][11][12][13] and 14-membered resorcylic acid lactones [14], and in our previous investigations, among them dibenzo-α-pyrones showed larvicidal activities [10]. Nevertheless, Hyalodendriella sp.…”
Section: Introductionmentioning
confidence: 99%